2022
DOI: 10.12998/wjcc.v10.i19.6656
|View full text |Cite
|
Sign up to set email alerts
|

Massive gastrointestinal bleeding after endoscopic rubber band ligation of internal hemorrhoids: A case report

Abstract: BACKGROUND Rubber band ligation (RBL) using rigid anoscope is a commonly recommended therapy for grade I-III symptomatic internal hemorrhoids. Severe complications of RBL include pain, hemorrhage and sepsis. Flexible endoscopic RBL (ERBL) is now more commonly used in RBL therapy but few severe complications have been reported. Here we report on a case of massive bleeding after ERBL. CASE SUMMARY A 31-year-old female was admitted to the department of gastroenterology wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Therefore, the tension of the ligature site can be reduced by root supplementary ligation and series ligation during ligation, so as to reduce the possibility of band removal. In addition, coagulation disorders [23], taking anti-platelet and/or acetylsalicylic acid [24] can increase the risk of bleeding related to ERBL. It is routinely recommended that patients should stop this medication for at least 1 week prior to, and 2 weeks post ERBL [25].…”
Section: Follow-up Outcomesmentioning
confidence: 99%
“…Therefore, the tension of the ligature site can be reduced by root supplementary ligation and series ligation during ligation, so as to reduce the possibility of band removal. In addition, coagulation disorders [23], taking anti-platelet and/or acetylsalicylic acid [24] can increase the risk of bleeding related to ERBL. It is routinely recommended that patients should stop this medication for at least 1 week prior to, and 2 weeks post ERBL [25].…”
Section: Follow-up Outcomesmentioning
confidence: 99%
“…There are few severe complications of ERBL that have been reported in the literature. Jiang et al [12 ] recently reported a case of massive gastrointestinal bleeding in a patient without underlying coagulopathy or anticoagulant/antiplatelet use, 7 days after ERBL of grade II hemorrhoids in which all five rubber bands that…”
Section: Endoscopic Rubber Band Ligationmentioning
confidence: 99%
“…There are few severe complications of ERBL that have been reported in the literature. Jiang et al [12 ▪ ] recently reported a case of massive gastrointestinal bleeding in a patient without underlying coagulopathy or anticoagulant/antiplatelet use, 7 days after ERBL of grade II hemorrhoids in which all five rubber bands that were deployed had slipped off leaving multiple bleeding ulcers at the site. However, more data is needed in the future with larger sample sizes, and with improved standardization of candidate selection and technique, to analyze the serious complications of ERBL, particularly massive gastrointestinal bleeding.…”
Section: Endoscopic Rubber Band Ligationmentioning
confidence: 99%
“…The use of office-based techniques, not requiring anaesthesia and hospitalization, mitigates but does not eliminate this risk. Rubber band ligation (RBL), reported as the most effective ambulatory technique for the treatment of haemorrhoidal disease, may rarely be associated with severe late bleeding (13), often occurring between the 10th and 14th postoperative day, and this risk is increased in patients on anticoagulant therapy (14, 15).…”
Section: Introductionmentioning
confidence: 99%